Mechanical properties and characteristic analysis of the new concave–convex polypropylene macro fiber. (April 2019) - Ding, Chunlin; Wu, Chao; Meng, Zhewei; Fang, Gang
A computer-controlled electronic universal testing machine was used to test the mechanical properties of polypropylene macro fiber, including tensile strength, breaking elongation, and elastic modulus. The mechanical properties were compared with fibers soaked in an alkali solution and heat treated. The dispersion, corrosion resistance, and toughness of the polypropylene macro fiber in concrete were also analyzed via a fiber concrete test. The polypropylene macro fiber has a high tensile strength, large elastic modulus, and good ductility. The polypropylene macro fiber has heat resistance and alkali resistance. After heat treatment, the maximum breaking force, tensile strength, elastic modulus, and elongation at breaking are more than 92.0% of baseline. After alkali solution treatment, the maximum breaking force, tensile strength, elastic modulus, and elongation at breaking reach more than 88.0% of baseline. The surface of the polypropylene macro fiber is concave and convex; the cross section is X type, and the bite force is powerful between the concrete and the fiber. Compared to steel fiber, the polypropylene macro fiber is light and small. At the same volume content, the input number of the polypropylene macro fiber per volume concrete is more than that of steel fiber, and it is easy to evenly disperse the material. It has corrosion resistance and high toughness when the polypropylene macro fiber is mixed in the concrete.